Effects of intermittent loading on fatigue life of a high strength steel in very high cycle fatigue regime. (December 2018) - Sun, Chengqi; Song, Qingyuan; Hu, Yuanpei; Wei, Yujie
Highlights: Intermittent loading improves fatigue life of a high strength steel in VHCF regime. No difference is observed for crack initiation site and fracture surface by SEM. The phenomenon is ascribed to strain aging by numerous low stress amplitude cycles. Abstract: An intermittent loading path (i.e. a pause duration follows after a loading pulse) is broadly employed in a ultrasonic fatigue test to minimize the effect of self-heating in specimens. The exact influence of such intermittent loading strategy remains elusive. We report here a significant fatigue life improvement of a high strength steel in very high cycle fatigue regime subjected to intermittent loading, in contrast to that without the pause duration although the crack initiation mechanism remains the same. This phenomenon is attributed to the strain aging by the numerous low stress amplitude cycles under intermittent loading, which strengthens the local region ahead of the initiated crack tip by the former high stress amplitude cycles and improves the fatigue life.